Euro 2012: Analysis and evaluation of goals scored - Leite, W. S. S. (International Journal of Sports Science, 2013)
The aim of this study was to analyze and quantify, in absolute and percentage terms, the goals scored in Euro 2012; verify in which periods and times of the matches goals happen, over total time of the game; the first goal`s impact to final result of the match; and way of attack that teams scored goals during the tournament. Then establish relationship between the results and the physical, technical, tactical and psychological aspects. We performed a quantitative study which examined 31 matches, by analyzing the official dockets, that are available in the database of UEFA's official website and videos with the goals scored were also used. The results show that most goals (57.89%) were marked in the second half of the game. The team that scored the first goal was the winning team in 70.97% of the games. Regarding modes of attack used to score goals, the organized attack (44.1%) was the most used. Given these results, we can say that the physical performance affects the technical, tactical and psychological performance of team directly.